Military-Political Confrontations In The Khanates Of The South Caucasus In 1768-1774 And Erekle II - David Merkviladze (Banber Arevelagitut'yan Instituti)
In 1768, Fatali Khan of Quba together with Hussein Khan of Shaki took Shamakhi. Soon, however, the former also tried to subdue the Shaki Khanate. For this purpose, Fatali offered King Erekle II of Kartli-Kakheti and Ibrahim Khan of Karabakh to campaign against the Shaki Khanate. But failed to get their consent. For his part, the Khan of Shaki asked Erekle II for help. The King demanded that Fatali Khan reconcile with the Khan of Shaki and threatened to provide military assistance to Hussein Khan.Ibrahim Khan of Karabakh also asked Erekle II for help in case of Fatali Khan’s aggression. Thus, an alliance between Erekle II, Hussein Khan and Ibrahim Khan against Fatali Khan was formed. The allies aimed to restore the rule of Aghasi Khan in Shamakhi, even on the condition of vassalage to Fatali Khan. In case of refusal, they intended to return the Quba Khanate to its former borders.The Russian government tried to limit the activity of Erekle II in the ongoing confrontation between the South Caucasian Khans. Nevertheless, in 1770, Erekle II sent an army to Ibrahim Khan of Karabakh to repel the attack of Fatali Khan. As a result, Fatali Khan’s campaign in Karabakh ended in failure. In November-December 1773, the Avar Khan Muhammad-Nutsal IV, along with Hussein Khan and Aghasi Khan, campaigned to Shamakhi. King Erekle helped the Avars militarily. Erekle II sent a detachment of Muslim Borchaly Kazakhs against Fatali Khan, in order to make the participation of his subordinates less noticeable. But this did not go unnoticed by Russian intelligence. At the same time, it is incorrect to name Erekle II as an ally of the Dagestani leaders united against Fatali Khan in the subsequent campaign of 1774. The King’s participation in the hostilities during this campaign is not confirmed by any source.